Emotional distress with dementia: a systematic review using corpus‐based analysis and metaethnography - Petty, Stephanie; Harvey, Kevin; Griffiths, Amanda; Coleston-Shields, Donna Maria; Dening, Tom (Wiley, 2018)
Objective: More understanding is needed about the emotional experiences of dementia from the perspective of the individual. This understanding can then inform the provision of health care to meet individual needs. This systematic review aimed to present all available descriptions of emotional distress and explanations for emotional distress experienced by individuals with dementia, articulated personally and by others. Methods: A systematic mixed‐method review identified literature that was screened and quality appraised. Data were analysed quantitatively and qualitatively using corpus‐based methods and meta‐ethnography. Results: The 121 included studies showed that individuals with dementia have expressed emotional distress comprehensibly. Family, professional caregivers, clinicians, and academic writers have also observed and described extreme emotional experiences. Feeling fearful and lonely were predominant and show the importance of anxiety in dementia. Explanations for emotional distress included threats to universal, human needs for identity, belonging, hope, and predictability. Conclusions: The variable and personal emotional experiences of individuals with dementia are well described and should not continue to be overlooked. Limitations, future research, and clinical implications are discussed.